PENGARUH BEBAN PAJAK TANGGUHAN, BEBAN PAJAK KINI, PERENCANAAN PAJAK, LEVERAGE DAN KOMPENSASI MANAJEMEN TERHADAP MANAJEMEN LABA (Studi pada Perusahaan LQ 45 yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Annisa, Yosy; Sari, Ria Nelly; Afriana, Rheny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine: (1) the effect of the deferred tax burden on earnings management, (2) the effect of current tax burden on earnings management, (3) the influence of tax planning on earnings management, (4) leverage effect on earnings management and (5) the effect of management's compensation on earnings management. The population in this study are 45 companies included in LQ 45 listed on Indonesia Stock Exchange in 2013-2016. In this research the sample used is 23 companies selected by using purposive sampling method. This study uses secondary data obtained from the website www.idx.co.id. The method of analysis used in this study is multiple linear regression analysis. Hypothesis test is done by t test and coefficient of determination test.The results of this study indicate that (1) the deferred tax burden affects earnings management, (2) the current tax burden has no effect on earnings management, (3) tax planning affect the earnings management, (4) leverage affect the earnings management and (5) compensation management management against earnings management.Keywords : Earning Management, Deffered Tax Expense, Current Tax Expense, tax Planning, Leverage and Management Compensation.